The Necessity and Prospects for Modernizing Higher Education Management in Uzbekistan - Bakhonov Bekhruz Anvarovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the necessity and prospects of modernizing higher education management in Uzbekistan. It analyzes the existing challenges in the higher education system, their underlying causes, and possible directions for improving management efficiency. Special attention is given to the implementation of modern management mechanisms, the use of digital technologies, the adoption of international experience, and the democratization of the educational process. The findings indicate that modernizing higher education management will enhance the country’s intellectual potential and strengthen its position in the global educational space.